Analisis Restorative Justice dalam Penelantaran Anak Pasca Cerai di Kabupaten Gorontalo - Windy Olivia Dawa; Roy Marthen Moonti; Ibrahim Ahmad; Muslim A. Kasim (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This study aims to analyze the application of restorative justice in handling cases of child neglect after divorce in Gorontalo Regency. The main focus of this study is to ensure the fulfillment of children's rights, reduce parental conflict, and minimize negative impacts on children. The formulation of the problem in this study includes: how to apply restorative justice in cases of child neglect after divorce, and how to be held accountable for criminal acts of child neglect after divorce. By using the juridical-empirical method and descriptive-analytical approach, this study uses data from literature studies such as journals, legal documents, laws and regulations. As well as qualitative data analysis from the BPS of Gorontalo Regency. The results of the study indicate that restorative justice is effective in creating humane solutions through constructive dialogue that ensures that children's custody, livelihood, and emotional needs are met.